Acute Toxicity of Mercury Chloride (Hgcl2) and Cadmium Chloride (Cdcl2) on the behavior of freshwater fish, Percocypris Pingi - Dengyue Yuan; Lan Huang; Ling Zeng; Sheng Liu; Zhengjian He; Ming Zhao; Jupan Feng; Chuanjie Qin (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2017)
The present study was performed to examine acute toxicity of two water-borne metals (Hg and Cd) by static bioassays. Fingerlings Percocypris pingi (P. pingi) were exposed to a range of concentrations of heavy metals and the mortality rate were investigated after 24, 48, 72 and 96h. The median lethal concentration (LC50) was determined with Probit analysis. The LC50 values of mercury chloride for the P. pingi at 24, 48, 72 and 96h were 0.441, 0.347, 0.327 and 0.327 mg/L, respectively. But the LC50 values of cadmium chloride at 24, 48, 72 and 96h were 2.551, 2.341, 1.207 and 0.081mg/L, respectively. The toxicity ranking of the two heavy metals was Hg>Cd. The safe concentration of Hg and Cd were 0.0327 and 0.0081mg/L, respectively.